Dinamika Hukum Perpajakan Di Indonesia Ditinjau Dari Undang-Undang Nomor 28 Tahun 2009 Tentang Pajak Daerah Dan Distribusi Daerah - Moza Dela Fudika; Rosyidi Hamzah (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
Changes in tax regulation policies as an implication of regional autonomy in Indonesia starting from Law Number 18 of 1997 concerning Regional Taxes and Regional Levies, then amended by Law Number 34 of 2000 concerning Amendments to Law Number 18 of 1997 concerning Taxes Regions and Regional Retribution. This regulation was later replaced by Law Number 28 of 2009 concerning Regional taxes and Regional Levies. Of the three regulations, legal dynamics occur that lead from decentralized to centralized. The research method in this study uses the normative legal method. From the results of the study, it is found that the dynamics of taxation law in Indonesia in terms of law number 28 of 2009 concerning regional taxes and regional distribution have experienced legal changes in terms of types of taxes, discretionary rate setting, and the nature of determining the type of tax of the law prevailing previously which led to a decentralized to centralized nature as well as a change in tax determination policy from an open list system to a closed list system. Keyword : legal dynamics, taxation, regional taxes and regional distribution